Shell shape polymorphism analysis of the Manila clam Ruditapes philippinarum across different geographical populations in China - Huo, Zhongming; Wang, Zixuan; Li, Dongdong; Liu, Kuo; Li, Xiaotong; Fang, Lei; Yan, Xiwu (Frontiers in Marine Science, 2024)
Morphology of bivalves, a kind of quantitative character, is closely connected with the ecological and physiological behaviors of bivalves, including growth, survival, metabolism and reproduction. In this study, a multivariate statistical method was used to analyze seven indices for shell shape evaluation of Ruditaps philippinarum (R. philippinarum). Polymorphism of R. philippinarum shell shape across seven geographical populations from the southern and northern regions of China was revealed, and decisive effect of shell shape in determining the trait of weight was discussed. In total, three types of R. philippinarum shell shape were observed: globular, flat, and lateral-view round. The Laizhou (LZ) population from the north of China displayed an approximately globular shell shape, with a shell-width-to-shell-length ratio of 0.5496 and an ellipse index ventral view (EIV) value of 0.9543. The Lianjiang (LJ) population from the south of China displayed a flat shell shape, with a shell-width-to-shell-length ratio of 0.4044, an ellipse index lateral view (EIL) value of 1.2518, and an EIV value of 0.7063. The Zhangzidao (ZZD) population from the north of China displayed a lateral view round shell shape, with a shell-width-to-shell-length ratio of 0.7476 and a circle index lateral view (CIL) value of 0.7195. According to the results of principal component analysis (PCA), discriminant analysis and cluster analysis on shell shape parameters, LJ population and LZ population could be grouped separately. However, despite the long geographical distance, Rongcheng (RC) population was highly similar with ZZD population in terms of shell shape traits, implying that these two populations might be more closely related. Lowest degree of divergence in shell shape was observed in Beihai (BH) population and Yingkou (YK) population, both of which belonged to Zuidong (ZD) population. Weight of globular Manila clams was significantly higher than that of flat clams (P < 0.05). This study not only lays a foundation for conservation of R. philippinarum germplasm resources, but also highlights the importance of considering shell morphology in the breeding and culture of R. philippinarum.